Innovating Traditional Culinary Products: Developing ‘Karipap’ as a Creative Economy Driver in Payakumbuh Cultural Village - Insan, Ranggi Rahimul; Holinesti, Rahmi; Mustika, Sari; Utami, Riski Gusri; Rahmatunisa, Risma; Siregar, Juliana; Rosel, Ruhul Fitri (Warta Pengabdian Andalas, 2025)
The Balai Kaliki Cultural Village in Payakumbuh City holds great potential for developing a creative economy rooted in traditional Minangkabau culinary heritage. However, this potential remains underutilized, particularly in terms of product innovation, packaging, and marketing. This community service program aimed to enhance the community’s skills in processing, packaging, and promoting innovative karipap products as a step toward developing local creative economy enterprises. The program was conducted in three stages: preparation, which included a needs assessment and coordination with local stakeholders; training, focused on hygienic food processing, innovative recipe development, packaging design, and social media–based branding; and evaluation and mentoring, which involved skill assessments and business sustainability planning. Ten participants, consisting of women and young women from the Family Welfare Movement (PKK), were selected purposively. The findings showed a significant improvement in participants’ knowledge and skills, with the average test score increasing to 85%. Participants successfully created three new product variations and established social media accounts for marketing purposes. Overall, this program successfully empowered the local community through skill enhancement in culinary innovation, packaging, and digital promotion. It contributes to the advancement of local creative economies while supporting the Sustainable Development Goals (SDGs), particularly poverty alleviation and food security, and reinforcing Minangkabau cultural identity through local culinary innovation.